The reality of the physical education lesson in the schools of Baghdad governorate from the point of view of the applied students - Hussien, ali; Ismaei, Karam; Znad, Bashar (Journal of Physical Education, 2023)
The lesson of physical education needs many things related to the reality of the student in it and the reality of the teacher and the requirements and tools required and the care of education and school administration for this lesson. Physical Education and Sports Sciences / University of Baghdad for the academic year 2022/2023, numbering (363) students, as they were chosen by the intentional method, The researchers used the descriptive approach to achieve the aim of the research, and the researchers used a questionnaire consisting of (4) axes, and the frequency and percentage were calculated. With sports supplies and the axis of school administration, the researchers recommended the necessity of conducting similar studies in the faculties of physical education and sports sciences.